2022
DOI: 10.1186/s40494-022-00814-2
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage and mechanical properties of drying oil paints

Abstract: Understanding how the evolving molecular composition of an oil paint layer on its transition to an aged solid film affects its dimensional change and mechanical properties is fundamental to the assessment of material durability and more broadly risk of degradation of oil paintings. Tensile properties—modulus of elasticity and strain at break—as well as cumulative shrinkage were determined for a selection of oil paints from Mecklenburg’s Paint Reference Collection now after approximately 30 years of drying. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In contrast to gesso, drying oils used as binders in oil paints solidify and harden through chemical reactions with oxygen. As indicated earlier, the molecular system of oil paints is continually evolving even after 30 years of drying under room conditions, and oil paints not only get stiffer and more brittle with the drying time but also experience increased cumulative shrinkage [4]. The hierarchical patterns visible in Fig.…”
Section: Hmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast to gesso, drying oils used as binders in oil paints solidify and harden through chemical reactions with oxygen. As indicated earlier, the molecular system of oil paints is continually evolving even after 30 years of drying under room conditions, and oil paints not only get stiffer and more brittle with the drying time but also experience increased cumulative shrinkage [4]. The hierarchical patterns visible in Fig.…”
Section: Hmentioning
confidence: 69%
“…The assumed magnitudes of drying shrinkage were indicated in Fig. 2 varying between 0.5% and 9% as determined for oil paint with lead white in [4]. The assumed ranges of evolving modulus of elasticity and strain at break were 1 -10 GPa and 1 -0.1 %, respectively.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Better control and understanding of the mechanisms governing the drying process of paint suspensions and their rheological properties present an undeniable interest for fundamental investigations. Recent studies deal with shrinkage, and the mechanical properties of drying oil paint or mechanical properties of artists paint-dried illustrate well the potential interest of the proposed investigations to practical applications.…”
Section: Introductionmentioning
confidence: 84%
“…Barbera et al [7] performed mechanical characterisation of 30-year naturally aged linseed-oil-based paint showing that the linear increase in stiffness for the first ten years is followed by an exponential trend in stiffness thereafter. In addition, Janas et al [33] recently performed a mechanical characterisation study on 29-year aged linseed-oil-based paints. The results of these studies showed that even after decades of ageing, the mechanical properties of these paints were still changing (becoming stiffer and more brittle).…”
Section: Materials Parametersmentioning
confidence: 99%